2013
DOI: 10.1111/j.1752-0606.2012.00332.x
|View full text |Cite
|
Sign up to set email alerts
|

How Many Bytes Does It Take? A Content Analysis of Cyber Issues in Couple and Family Therapy Journals

Abstract: In the fifteen years since the explosion of the Internet, using cyber technology for work and social functions has exponentially increased. Yet, questions around how to manage such changes remain elusive in family therapy literature. In this investigation, we conducted a content analysis to determine to what extent marriage/couple and family therapy (M/CFT) journals have responded to the integration of the Internet in couple and family life. We found 79 of 13,274 articles across seventeen journals focused on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 108 publications
(110 reference statements)
0
46
0
2
Order By: Relevance
“…Despite the fact that ICTs' use developed and expanded since the early 1990s, the literature regarding their influences on relationships and family life, their use in family therapy and training, the consequences of problematic use and the therapeutic strategies to face them, has not yet flourished within the systemic approach (see Blumer et al 2014 for a publication overview)-as distinct from other therapeutic perspectives (Saddichha et al 2014;Andersson 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that ICTs' use developed and expanded since the early 1990s, the literature regarding their influences on relationships and family life, their use in family therapy and training, the consequences of problematic use and the therapeutic strategies to face them, has not yet flourished within the systemic approach (see Blumer et al 2014 for a publication overview)-as distinct from other therapeutic perspectives (Saddichha et al 2014;Andersson 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Inertial sensors have also been used in wobble boards for training balance (see Table 1) [24,25,33]. These boards consist of an instable plate, which causes the user, while standing on the plate, to wobble, thereby controlling the game, for instance a ball in a maze [33], by shifting his weight in ML and AP directions.…”
Section: Introductionmentioning
confidence: 99%
“…These boards consist of an instable plate, which causes the user, while standing on the plate, to wobble, thereby controlling the game, for instance a ball in a maze [33], by shifting his weight in ML and AP directions. The movements are measured using a single orientation tracker (Xsens MTx Motion Tracker, Xsens Technologies, The Netherlands) which consists of three gyroscopes [36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because technology is such an integrated aspect of North American lifestyles (Cole et al, 2009;Duggan & Brenner, 2013;Rainie, 2010;Smith, 2012), therapists need to possess a reasonable amount of knowledge around the different types, uses, and implications of technology (Hertlein & Webster, 2008). Given the limited opportunities, it could be challenging for counselors to be informed of this topic (Blumer, Blumer et al (2014) found a limited and misrepresentation of the implications for technology use on couple and family relationships in counselor trainings and conference presentations, as well as in counseling literature. Similar to suggestions found in Hertlein and Blumer (2014), given the high rates of technology use within relationships, we recommend that therapists include a brief assessment (e.g., TIRA) of how technology influences client couples' intimate connections and relationship satisfaction.…”
Section: Therapeutic Implicationsmentioning
confidence: 97%